Special judo fitness test level and anthropometric profile of elite female cadet judokas - Casals, C.; Escobar-Molina, R.; Barranco-Ruiz, Y.; Huertas, J. R. (Revista de Artes Marciales Asiaticas, 2016)
maintaining an optimal body mass. The anthropometric profile of judokas is, therefore, a relevant factor for success in competition and for performance in specific judo tests, such as the Special Judo Fitnss Test (SJFT) developed by Sterkowicz (1995). The anthropometric variables that best predict SJFT performance have been determined in elite Spanish judokas from senior and junior divisions (Casals, et al, 2015), but not in cadets. Thus, the aim of the present study was to assess the mentioned relationship between body composition and specific performance in elite female cadet judokas.